Alias Anna : Zhanna Arshanskaya: a biography in verse : a true story of outwitting the Nazis - Hood, Susan, 1954- (Harper, an imprint of HarperCollinsPublishers, 2023)
"An inspirational nonfiction novel-in-verse about Zhanna Arshanskaya, a young Ukrainian Jewish girl using the alias Anna, whose phenomenal piano-playing skills saved her life and the life of her sister, Frina, during the Holocaust-from award-winning author Susan Hood, with Zhanna's son, Greg Dawson"-- $c Provided by publisher.